THE INFLUENCE OF SHARIA HOSPITALITY SERVICE ON INCREASING CUSTOMER VISITS AT COFFEE SHOP - Mona Ramadhani; Sitti Nikmah Marzuki; Jumriani (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to examine the effect of Sharia Hospitality Service on increasing customer visit intentions at Narama Coffee Shop Watampone. The background of this research is driven by the growing competition in the coffee shop industry, which requires business actors to provide not only high-quality services but also distinctive values based on Sharia principles. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 customers of Narama Coffee Shop. The data were analyzed using descriptive and inferential statistical techniques with the assistance of SmartPLS software. The findings reveal that Sharia Hospitality Service has a positive and significant effect on increasing customer visit intentions. Service dimensions such as tangibles, reliability, responsiveness, assurance, and empathy were found to enhance customer satisfaction, strengthen customer loyalty, and encourage revisit intention. These results support the Service Quality Theory and Disconfirmation Theory, which explain that customer satisfaction is formed through the alignment between customer expectations and the actual performance of the service received.